Early sexual initiation and long-term hormonal contraception: Cervical cancer risk in Makassar, Indonesia - Cahyani, Taty Pilar; Haruna, Nadyah; Setiawati, Dewi; Delima, Alifia Ayu; Lestari, Esa (Sociality: Journal of Public Health Service, 2025)
Cervical cancer remains a critical public health problem, particularly in low- and middle-income countries where access to early detection and prevention programs is limited. Previous studies have highlighted reproductive behaviors as important risk factors; however, region-specific evidence to inform targeted health interventions remains insufficient. This study aimed to examine the association between selected reproductive behaviors and cervical cancer incidence among women in Makassar, Indonesia. A cross-sectional analytic design was employed using medical record data from 147 women diagnosed with cervical cancer at Ibnu Sina Hospital between January 2023 and June 2024. Data were analyzed using chi-square tests and logistic regression to assess the relationships between early sexual initiation, number of sexual partners, long-term hormonal contraceptive use, and cervical cancer risk. The findings indicated that women who initiated sexual intercourse at or before the age of 20 were nearly four times more likely to develop cervical cancer. In addition, long-term use of hormonal contraception for more than five years was associated with a sixfold increase in risk. No significant association was observed between the number of sexual partners and cervical cancer, possibly due to sample homogeneity and reporting bias. These results underscore the importance of early reproductive health education and informed contraceptive counseling. Public health strategies should prioritize culturally sensitive education, human papillomavirus vaccination, and improved access to screening programs to reduce cervical cancer burden in similar settings.